The Effectiveness of Using E-learning at SMA Negeri 4 Gowa - Muh. Darwis; Erwin Erwin; Sirajuddin Saleh; Jamaluddin Jamaluddin; Muh. Nasrullah (Universitas Negeri Makassar, 2021)
This research was conducted for students of SMA Negeri 4 Gowa. This study aims to determine 1) the existence of content or learning materials that are relevant to the learning objectives, 2) use appropriate learning methods, 3) use learning media in various formats such as text, visual, video, multimedia, and others, 4) can occur synchronously or asynchronously. The research method used is quantitative research with a population of 585 people and a sample of 88 respondents. Data collection techniques used are observation, questionnaires, interviews, and documentation. The data analysis technique used is a descriptive percentage and distribution analysis. The results showed that the effectiveness of the use of e-learning at SMA Negeri 4 Gowa was classified as effective in terms of indicators of the existence of content or learning materials that were relevant to the learning objectives, using appropriate learning methods, using learning media in various formats such as text, visual, video, multimedia, etc., and can occur synchronously or asynchronously. To achieve effective use of e-learning, efforts are made to increase student interest in learning and also the availability of learning services to support the online learning process in the COVID-19 pandemic era.